Converting the Masses Advertising Nature and Gender in the Post #MeToo Movement Era - Nichols, Amanda M. (2021)
Drawing on the work of Naomi Wolf who described a transition in commercial advertising inspired by the feminist movement, I examine the ways commercial marketing strategies have changed in the wake of the election of Donald Trump and the #MeToo movement. This shift illuminates the ideological functions of advertisements with regard to understandings of gender and nature. Employing Benson Saler's family resemblances approach, and further drawing on the work of David Chidester and Katheryn Lofton I show that advertisements function in religion-resembling ways in pop culture. By examining a number of corporate advertisements between 2004 and 2019, I show a shift in some corporations'marketing strategies in light of political tensions concerning sexual harassment and climate change in the United States. These changing strategies also represent a call to action by forming community around shared causes, urging consumers to choose wisely and think about something bigger than themselves.
Keywords: #MeToo; Commercial advertising; Donald Trump; Gender; Nature; Religion